Validation of a coupled multibody and TEHL simulation by a piston/cylinder component test rig. (November 2022) - Kroneis, Markus; Scheerer, René; Bobach, Lars; Bartel, Dirk
A tribological highly stressed contact in the actuating system of axial piston machines is located between the control piston and the control chamber. This paper presents a new type of component test rig for measuring the frictional force and the gap heights between piston and cylinder. For this purpose, the original system is reduced to the actuator system, whereby the real kinematics and the loading forces are maintained. The axial movement of the control piston and the pressure in the control chamber can be configured individually. The measurement results of different parameter variations are compared with the results of the simulation. The simulation based on a coupled multibody and TEHL simulation with a transient, three-dimensional, thermal elastohydrodynamic contact calculation.